Meningkatkan Aktivitas Dan Motivasi Menggunakan Model Ceria Pada Siswa Kelas 3 SDN Kelayan Timur 13 - Fauziah Safara; Noorhapizah . (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problems that occur in this study are low activity and lack of student motivation in learning Mathematics. Alternative problem solving in this study uses the CERIA model. This study aims to analyze student activity and motivation. This research is a class action research using quantitative and qualitative approaches. The form of research uses Classroom Action Research (PTK) for 4 meetings. Third grade students of SDN Kelayan Timur 13 even semester of 2023/2024 totaling 20 students were the selected research subjects. Data collection techniques in the form of teacher activity instruments, student activities and student motivation. The results showed that teacher activities were carried out up to a score of 100% very good category, student activities were carried out up to a score of 90% very active category, motivation was carried out up to a score of 85% very high category. Based on these findings it can be concluded that using the CERIA model can increase student activeness and student motivation. It is recommended to use this model as an alternative tool in increasing student activity and motivation